2005
DOI: 10.1161/circulationaha.104.508465
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein in Heart Failure

Abstract: CRP is increased in heart failure. Higher levels are associated with features of more severe heart failure and are independently associated with mortality and morbidity. The ability of treatments to reduce CRP levels and the prognostic importance of reducing CRP require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
0
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(154 citation statements)
references
References 30 publications
10
131
0
13
Order By: Relevance
“…RELAX included S‐HFpEF patients while DOSE and ROSE included acutely decompensated HF (ADHF) patients with both HFrEF and HFpEF. IL‐6, TNF‐α, and hs‐CRP were selected because of the long‐standing experience with their use in HF10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and PTX3 because of its association with vascular inflammation21 and ability to risk‐stratify HF patients. Each trial was approved by the Institutional Review Board at each participating site, and all patients provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RELAX included S‐HFpEF patients while DOSE and ROSE included acutely decompensated HF (ADHF) patients with both HFrEF and HFpEF. IL‐6, TNF‐α, and hs‐CRP were selected because of the long‐standing experience with their use in HF10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and PTX3 because of its association with vascular inflammation21 and ability to risk‐stratify HF patients. Each trial was approved by the Institutional Review Board at each participating site, and all patients provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have revealed a significant correlation between elevations in blood levels of pro‐inflammatory biomarkers such as tumor necrosis factor alpha (TNF‐α), C‐reactive protein (CRP),interleukin 6 (IL‐6), and HF severity and prognosis 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. Recently, pentraxin 3 (PTX3), an acute‐phase reactant member of the CRP super family expressed by a variety of cell types in response to various inflammatory stimuli21 and thought to be a marker of vascular inflammation, was found to facilitate risk stratification of HF patients 22, 23, 24, 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several new biomarkers have emerged as strong predictors of risk among patients presenting with cardiovascular disease, including CHF. Among them, cardiac troponin I (cTnI) and T, 2 B-type natriuretic peptide (BNP), 3 N-terminal pro-B-type natriuretic peptide (NT-proBNP) 4 and high-sensitivity C-reactive protein (hsCRP) 5,6 are easy to measure and such measurement is now routinely available to clinicians. Sabatine et al have demonstrated that simultaneous assessment of cTnI, CRP, and BNP could enable clinicians to stratify risk more effectively among patients with acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuating inflammatory responses associated with HF may potentially represent another drug target (e.g. by use of angiotensin II receptor blocker, ω‐3 polyunsaturated acids) 32, 33. The randomized PICNIC study is currently evaluating the impact of nutritional intervention on morbidity and mortality in malnourished hospitalized HF patients with and without hypoalbuminemia 34.…”
Section: Discussionmentioning
confidence: 99%